Determinants of Systematic Risk in Commercial Banks of Pakistan - Shah, Syed Fahad Ali; Hussain, Arif; Khan, Muhammad; Jacquemod, Julija; Shah, Zahir (International Journal of Economics and Financial Issues, 2020)
Various efforts are made to quantify and explain risk taking behavior including systematic risk with in financial institutions. This study is about determining various factors affecting commercial banks systematic risk in Pakistan. Sample included in the study consisted of twelve commercial banks listed in PSX (Pakistan Stock Exchange), these banks hold 81.3% market share of customer deposits. Data was collected from 2010 to 2016. The systematic risk for this study was calculated through stock beta (SB) and value at risk (VaR). To determine systematic risk the independent variables used are liquidity, firm size, asset quality, firm growth, return on assets, business mix, operating efficiency and loan growth. The result shows that liquidity, asset quality, return on assets and firm size have significant impact on systematic risk of banks in Pakistan. Keywords: Systematic risk, Asset quality, Operating efficiency, Business mix JEL Classifications: G21, G32 DOI: https://doi.org/10.32479/ijefi.9794